2022
DOI: 10.1152/ajprenal.00053.2022
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibition effect on salt-induced hypertension, RAAS, and Na+ transport in Dahl SS rats

Abstract: SGLT2 inhibitors are the new mainstay of diabetes mellitus and cardiovascular diseases treatment. Despite the remarkable benefits, the molecular mechanisms mediating the effects of SGLT2 inhibitors on water and electrolyte balance are incompletely understood. The goal of this study was to determine whether SGLT2 inhibition alters blood pressure and kidney function via affecting the Renin-Angiotensin-Aldosterone System (RAAS) and sodium channels/transporters along the nephron in Dahl Salt-Sensitive (SS) rats, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 82 publications
3
12
1
Order By: Relevance
“…In correlation with these findings, the mRNA expression of ENaC was increased in enlarged collecting ducts of EMPA-treated animals ( Figure 4A ) supporting the proposed concept of increased reabsorption workload in this segment. The rather small effect on mRNA expression of the ENaC subunits was not found on protein level ( Supplementary figure S5 ) and the literature is very contradictory regarding the regulation of renal sodium transporters by SGLT2 inhibitors ranging from no effect ( Chen L. et al, 2016 ; Kravtsova et al, 2022 ), reduced expression ( Chung et al, 2019 ) or increased expression ( Ma et al, 2019 ). It has to be mentioned that only this study used healthy wildtype animals, while most expression analysis data derive from rodent disease models for diabetes or salt-induced hypertension, treatments known to affect renal Na + handling itself.…”
Section: Discussionmentioning
confidence: 99%
“…In correlation with these findings, the mRNA expression of ENaC was increased in enlarged collecting ducts of EMPA-treated animals ( Figure 4A ) supporting the proposed concept of increased reabsorption workload in this segment. The rather small effect on mRNA expression of the ENaC subunits was not found on protein level ( Supplementary figure S5 ) and the literature is very contradictory regarding the regulation of renal sodium transporters by SGLT2 inhibitors ranging from no effect ( Chen L. et al, 2016 ; Kravtsova et al, 2022 ), reduced expression ( Chung et al, 2019 ) or increased expression ( Ma et al, 2019 ). It has to be mentioned that only this study used healthy wildtype animals, while most expression analysis data derive from rodent disease models for diabetes or salt-induced hypertension, treatments known to affect renal Na + handling itself.…”
Section: Discussionmentioning
confidence: 99%
“…Urine and serum were obtained from dapagliflozin- and vehicle-treated hypertensive animals as described in a previous study by Kravtsova et al 44 and analyzed as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Urine and serum were obtained from dapagliflozin-and vehicletreated hypertensive animals as described in a previous study by Kravtsova et al 44 and analyzed as described previously. Each fecal sample was transferred to a sealed bag containing a CO 2 gas pack (BD GasPak EZ pouch system) immediately, as described, 45 and was processed within 4 hours after defecation.…”
Section: Targeted Metabolomics Of the Dahl Salt-sensitive Hypertensiv...mentioning
confidence: 99%
“…The potential use of Na + -glucose cotransporter-2 inhibitors (SGLT2i) in salt-sensitive HTN and associated renal diseases has also generated much interest. A recent study found that dapagliflozin 2 mg/kg/day ameliorated HTN, improved pressure natriuresis and increased urinary flow rate, glucosuria, and Na + - and Cl − -to-creatinine ratios in Dahl salt-sensitive rats ( Kravtsova et al, 2022 ). Interestingly, in that study, no changes in the expression of RAAS metabolites or in Na + channels SGLT2, NKCC, NHE3, NCC and ENaC was observed.…”
Section: Treatment Of Salt-sensitive Htnmentioning
confidence: 99%